PENGARUH PENDEKATAN TEACHING at the RIGHT LEVEL (TaRL) TERHADAP PEMAHAMAN KONSEP MATEMATIS BERBANTUAN APLIKASI GEOGEBRA DI MTS AR-RASYID - Putri Sahara; Ely Syafitri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
The research was motivated by the researcher's interest in improving students' mathematical concept understanding at MTS Ar-Rasyid. The purpose of this study was to determine the effect of the GeoGebra-Assisted TaRL approach on the problem-solving abilities at VIIIth-grade students of MTS Ar-Rasyid. This study used a quasi-experimental approach with a two-group pretest-posttest design. The population are all VIIIth-grade students of MTS Ar-Rasyid. The subjects are students at VIIIth-A class  as the experimental class using the GeoGebra-Assisted TaRL approach and VIIIth-B class as the control class using the direct learning model. The materials used in this study were cubes and cuboids. After completing the learning, a posttest was given with an average result of the experimental class of 75,6000 and the control class of 58,6400. The results of the t-test obtained     then  was accepted, thus a significant influence was obtained by using the TaRL approach Assisted by the Geogebra Application on the Mathematical Concept Understanding Ability of Students at VIIIth grade students of MTS Ar-Rasyid.